Infants' center bias in free viewing of real-world scenes. (January 2019) - van Renswoude, Daan R.; van den Berg, Linda; Raijmakers, Maartje E.J.; Visser, Ingmar
Abstract: This study examines how salience and a center bias drive infants' first fixation while looking at complex scenes. Adults are known to have a strong center bias, their first point of gaze is nearly always in the center of the scene. The center bias is likely to be a strategic bias, as looking towards the center minimizes the distance to other parts of the scene and important objects are often located at the center. In an experimental design varying salience regions of scenes and start positions we examined infants' (N = 48, Age = 5–20-month-olds) first fixation after scene onset. The pre-registered hypothesis that infants also have a center bias while looking at real-world scenes was confirmed. The strength of the center bias is correlated with the saliency distribution such that the bias is weaker when the strongest salience is peripheral rather central. In the absence of clear salient regions there still was a strong center bias. These results suggests there is a competition between stimulus-driven factors and a center bias in steering attention from a young age onwards.